PENGARUH METODE MULTI SHUTTLE TERHADAP KEMAMPUAN PSIKOMOTORIK TEKNIK DROPSHOT DAN LOB DALAM PEMBELAJARAN BULU TANGKIS SISWA SMAN 2 PROBOLINGGO - Akhmad Raikhan Nur Iswin; Rubbi Kurniawan; Anangga Widya Pradipta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the multi shuttle method on students' psychomotor ability in performing dropshot and lob techniques in badminton learning at SMAN 2 Probolinggo. The study used a quantitative pre-experimental approach with a one-group pretest-posttest design. The sample consisted of 30 students who participated in six badminton learning sessions using multi shuttle practices. Data were collected through performance tests of dropshot and lob techniques, assessed with a psychomotor rubric covering preparation, footwork, swing-contact, accuracy, and follow-through. Data analysis involved descriptive statistics, shapiro-wilk normality test, Levene's homogeneity test, paired sample t-test, N-Gain, and learning mastery analysis. The results showed an increase in the mean psychomotor score from 58.95 in the pretest to 81.78 in the posttest. The paired sample t-test indicated a significant difference between pretest and posttest scores, t(29) = 37.52, p < 0.001. The average N-Gain was 0.56, categorized as moderate improvement. Learning mastery also increased from 0% in the pretest to 93.33% in the posttest based on the minimum mastery criterion of 75. These findings indicate that the multi shuttle method has a positive effect on students' psychomotor ability in dropshot and lob techniques. The method can be used as an alternative practical strategy in badminton learning because it provides repeated, varied, and game-like motor experiences.